2015
DOI: 10.1038/srep08083
|View full text |Cite
|
Sign up to set email alerts
|

A size-dependent constitutive model of bulk metallic glasses in the supercooled liquid region

Abstract: Size effect is of great importance in micro forming processes. In this paper, micro cylinder compression was conducted to investigate the deformation behavior of bulk metallic glasses (BMGs) in supercooled liquid region with different deformation variables including sample size, temperature and strain rate. It was found that the elastic and plastic behaviors of BMGs have a strong dependence on the sample size. The free volume and defect concentration were introduced to explain the size effect. In order to demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…According to their experiments, Ti-based BMG samples with a smaller diameter exhibit a larger plasticity, while the strength does not markedly change. Similar results have also been reported in other BMGs [158][159][160][161][162][163]. The size effect has been explained from the viewpoints of free volume content [157,162,163], flaw sensitivity [159], plastic zone [160], and elastic energy dissipation [161].…”
Section: Strength and Ductilitysupporting
confidence: 73%
“…According to their experiments, Ti-based BMG samples with a smaller diameter exhibit a larger plasticity, while the strength does not markedly change. Similar results have also been reported in other BMGs [158][159][160][161][162][163]. The size effect has been explained from the viewpoints of free volume content [157,162,163], flaw sensitivity [159], plastic zone [160], and elastic energy dissipation [161].…”
Section: Strength and Ductilitysupporting
confidence: 73%
“…Another study presented a thermodynamically constitutive model of MGs by extending an infinitesimal deformation approach, in which the multiplicative decomposition of deformation gradient and additive decomposition of free energy was considered 22 . Yao et al 23 developed a size-dependent constitutive model of MGs and found that the size effect is a crucial factor in micro forming processes. Being able to apply for MGs, the Zener-Hollomon approach was considered by Yao et al 7 , in which the temperature effects and strain rate alterations are included in the model to evaluate the high temperature tensile deformation process.…”
Section: Introductionmentioning
confidence: 99%